Pemetaan potensi usaha desa dan penerapan "Adwords" sebagai solusi menghadapi persaingan usaha pada BUMDes Bhuana Amertha Sari Desa Tampaksiring, Gianyar - Sumerta, I Komang; Rai, Anak Agung Gede (Penamas: Journal of Community Service, 2021)
Bali has a lot of potential for strong local wisdom and culture as a provision in creating an alternative economy so that it relies not only on one tourism sector. One alternative is to develop Village Owned Enterprises (BUMDes). Based on the results of observations with the BUMDes administrator Bhuana Amerta Sari, Tampaksiring Village, Gianyar Regency, it was found that the business development managed by BUMDes Bhuana Amerta Sari, Tampaksiring Village, Gianyar Regency is still not optimal. In addition, management is still conventional, and product marketing is not optimal and has not implemented digital-based marketing in the face of increasingly fierce business competition. To overcome these problems, activities are designed that can answer the problems of partners, namely Bimtek and FGD of village potential in business development in the face of business competition. The results are various village business potentials that BUMDes can develop, mapping of village potential using SWOT analysis to measure the scale of business priorities.